Why Do Subsidiaries Divest? The Role of Subsidiary Performance, Slack Resources, and Sunk Costs - Chen Lu-Jui; Lee Wen-Ruey; Hsu Yu-Hsuan (Asian Academy of Management Journal, 2023)
Subsidiaries are important in the global strategy of multinational enterprises (MNEs). However, in the face of uncertainty and competition, the decision to divest a subsidiary from a market becomes a critical decision for MNEs. This study suggests that the factors for divesting subsidiaries are related not only to the performance of the subsidiary but also to slack resources and sunk costs. It analysed 254 subsidiaries in Taiwan and found that the better the subsidiary’s performance is, the less it would decide to divest from the market. Additionally, it was found that the subsidiary with slack resources would be a moderating variable with a positive impact. In addition, the presence of sunk costs reinforces the positive effect of slack resources on the relationship between subsidiary performance and the non-divestment of the subsidiary. Overall, this study points to the significance of subsidiary performance on decision-making and explains the influence of slack resources and sunk costs.